Prediction of Microwave Signal Attenuation due to Dust and Sand Storms at (4-18 GHz): Case of study (south of Libya) - Sana Fadil , Nassir Abuhamoud (Journal of Pure & Applied Sciences, 2019)
Dust and sand storms attenuation is one of the major problems in utilization of microwave bands for terrestrial and satellite communication especially at desert  areas. This paper present  and implement a mathematical model to predict the microwave signal attenuation due to dust and sand storm in the southern region of Libya. The main input parameters for the model are visibility, signal frequency, the volume of dust particulars and  humidity. The presented model effectively predicts the microwave signal attenuation. The results show that  the  attenuation increases with frequencies and humidity and decreases with visibilities.  The study found out that the highest values of attenuation in south of Libya varies from 0.13to 9.78dB/km at humidity 60% at Ku-frequencies. The outcome of this study will facilitate the design of reliable communication systems via considering wireless attenuation characteristics due to atmospheric conditions which can enable mitigation of channel fading condition by adaptively selecting appropriate propagation parameters.